Identification of pulmonary vein reconnection gaps with high-density mapping in redo atrial fibrillation ablation procedures. Issue Volume 20:Issue FI 3(2018) (20th June 2017) - García-Bolao, Ignacio; Ballesteros, Gabriel; Ramos, Pablo; Menéndez, Diego; Erkiaga, Ane; Neglia, Renzo; Jiménez Martín, Marta; Vives-Rodríguez, Enrique
Abstract: Aims: Maps obtained by means of electroanatomic high-density mapping (HDM) systems have shown their use in the identification of conduction gaps in experimental atrial linear lesion models. The objective of this study was to assess the use of HDM in the recognition of reconnection gaps in pulmonary veins (PV) in redo atrial fibrillation (AF) ablation procedures. Methods and results: One hundred and eight patients were included in a non-randomized study that assessed the recognition of reconnection gaps in PV by means of HDM compared to a control group that received conventional non-fluoroscopic guidance with a circular multipolar catheter (CMC). Among the HDM group, adequate recognition of reconnection gaps was obtained in 60.99% of the reconnected PVs (86 of 141), a figure significantly higher than that achieved with analysis of CMC recorded signals (39.66%, 48 of 121; P  = 0.001). The number of applications and total radiofrequency time were also significantly lower in the HDM group (12.46 ± 6.1 vs. 15.63 ± 7.7 and 7.61 ± 3 vs. 9.29 ± 5; P  = 0.02, and P  = 0.03, respectively). At the 6-month follow-up, no statistically significant differences were found in recurrence of AF or any other atrial tachycardia between the HDM group (8 patients, 14.8%) and the control group in (16 patients, 29.6%; P  = 0.104). Conclusion: An analysis of the high-density activation maps allows greater precision in the identification of reconnection gaps in PV, which results in lower radiofrequency time for the new isolation.